The Socio and Labor Conditions of Sex Workers in Quito, Ecuador (2017-2019) - Pérez Larrea, Nilka Marina (2020)
The purpose of this article is to understand the socio-labor conditions experienced by sex workers,part of a qualitative, phenomenological research, with the in-depth interview technique, in peopleover 40 years of age working in the streets and squares of the Historic Center Quito. In the findingsof the daily world of women there is a lack of labor rights, precariousness, unworthy wages, insecurity,inequity, poverty, discrimination and violence, which affects the physical and mental health ofthem and their families, this is further increases by the lack of recognition as a job and by the statusthat society has given women sex workers.